A Simple Method to Compute Fiscal Multipliers - Batini, Nicoletta (IMF Working Papers; Working Paper ;, 2014)
Fiscal multipliers are important tools for macroeconomic projections and policy design. In many countries, little is known about the size of multipliers, as data availability limits the scope for empirical research. For these countries, we propose a simple method-dubbed the 'bucket approach'-to come up with reasonable multiplier estimates. The approach bunches countries into groups (or 'buckets') with similar multiplier values, based on their characteristics. It also takes into account the effect of some temporary factors, such as the state of the business cycle.